Extending health care to afdc recipients who obtain jobs: Results of a demonstration - Rofuth, T.W.; Weiss, H. (Health and Social Work, 1991)
This study investigated the outcomes of a demonstration project that provided free medical coverage to former Aid to Families with Dependent Children (AFDC) recipients who were holding jobs with limited or no health benefits. Data were collected on the Medicaid expenditures of 54 eligible participants and their dependents for up to two years before they exited welfare; the expenditures averaged 56 percent less for adults and 45 percent less for children than the respective AFDC averages for the county. Because only 22 percent of the eligible participants took advantage of the program, telephone interviews also were conducted with 24 people who did not participate in or dropped out of the health plan. The main reasons cited for not enrolling were a misunderstanding of the program, a claim that no notification of the program was received, and a lack of interest. These results and their policy implications are presented in the context of the Family Support Act's mandate that states extend medical assistance coverage to AFDC recipients whose cases are closed because of employment. © 1991 by the National Association of Social Workers, Inc.
4 citations (Crossref) [2023-10-31]
Keywords: Aid to Families with Dependent Children; Cost-Benefit Analysis; Employment; Female; Health Education; Health Expenditures; Human; Insurance; Health; Male; Maryland; Medicaid; United States; article; cost benefit analysis; dept.swk; economics; employment; female; health care cost; health education; health insurance; human; male; medicaid; organization and management; social security; standard; utilization review

No easy answers and A delicate balance - Siegel, Elbert (Gerontologist, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-129-764-057-755 tex.type: [object Object]
Keywords: dept.swk